L’entrave aux politiques locales d’aménagement durable d’un territoire - Nicolas Buclet (Territoire en Mouvement)
To design the future of a territory supposes a capacity of influencing the main variables which structure the territory. Through two very different examples, the paper highlights that some essential variables are not controlled by local deciders. Yet, the French Sustainable Development National Strategy (SNDD) does not take this limit into account. The SNDD, in particular, asks to the territories to locally implement national objectives, without questioning the limits of a local action. The paper wonders about the need to integrate the questions of the determination of collective objectives as well as relations between territory projects and the market.